The nature of the universe - Buda, Stanisław (Hybris, 2013)
I would like to share a few reflections on the broader nature of the Universe, including also the nature of our research over it. This subject requires a philosophical approach that goes far beyond cosmology, or even the philosophy of nature. On the other hand, the traditional ontological considerations are too general — concern for the rules and the structure of reality. I start from definition of terminology, distinguishing: cosmos, the Universe, Meta-Universe, world, reality. Then I discussing some ontological conditions of being real at all. A reflection of this type enables and set a formal paradigm of inquiry on the nature of the Universe, which I understand as a whole, which consists of everything actually is. Then considering the formal status of that total, which turns out to be a dynamic system constantly generates its own “lack of coherence” and also “overcoming” it. It confronts us with the problem of generating and assimilating of Otherness. Therefore, I consider the universe as an Act, which, in a very sophisticated way, refer to its source and its reason. Calling for the need for more detailed considerations concerning the nature of the universe, speak a few comments with re-gard to the distinctive style of expression taking up the issue of physical Theory of Everything.